Stakeholder Involvement in Data collection for M&E and Performance of Literacy and Numeracy Educational Programme in Public Primary Schools in Nairobi County, Kenya - Karimi, Stella Silas; Mulwa, Angeline Sabina; Kyalo, Dorothy Ndunge (American Journal of Education and Learning, 2020)
Kenya’s education has faced many challenges especially in terms of literacy and numeracy skills. This has been caused by swelling enrolment in schools. The purpose of this article is to establish the extent to which Stakeholder Involvement in data collection influence performance of literacy and numeracy educational programme. Despite numerous initiatives by key educational stakeholders to improve the performance of learners, there has been limited achievement on learner skills. This study adapted descriptive research survey design and correlational research design. Data collected from the respondents by use of questionnaires and interview guide from a target population of 2053 and a sample size of 335. Data was analyzed using SPSS version 25 and results presented in tables and figures. Pearson moment correlation coefficient (r) were computed. The coefficient of determination R2 is 0.436 indicating that R2 was the coefficient of determination of this model and depicted that data collection explained 44%. The remaining 56% was explained by other factors. The overall F statistics 215.779 with p- 0.000b<0.05 implying a statistical significant relationship between data collection and performance of literacy and numeracy educational programme. Recommendations were policy makers should embrace the methodology of engaging all the stakeholders in collecting data. The results showed that Stakeholder Involvement in data collection strongly influenced the performance of literacy and numeracy educational programme as shown by a correlation coefficient, which was statically significant. Recommendations for further research on data management which was lacking and specifically involvement of all stakeholders in data collection in intervention of programme.